A performance comparison of Mobile IPv6, Hierarchical Mobile IPv6, fast handovers for Mobile IPv6 and their combination. - Pérez-Costa, Xavier
Mobile IP, the current IETF proposal for IP mobility support, represents a key element for future All-IP wireless networks to provide service continuity while on the move within a multi-access environment. We conducted a performance evaluation of Mobile IPv6 and its proposed enhancements, i.e., Fast Handovers for Mobile IPv6, Hierarchical Mobile IPv6 and our proposed combination of them, using the network simulator ns-2 for the case of a 'hot spot' deployment scenario. The simulation scenario comprises four access routers and up to 50 mobile nodes that communicate in accordance with the IEEE 802.11 wireless LAN standard. The study provides quantitative results of the performance improvements obtained by the proposed enhancements as observed by a single mobile user with respect to handoff latency, packet loss rate and achieved bandwidth per station. As a complementary part of the study, the signaling load costs associated with the performance improvements provided by the enhancements has been analyzed. The simulation environment allowed us also to investigate the behavior of the protocol in extreme cases, e.g., under channel saturation conditions and considering different traffic sources: CBR, VoIP, Video and TCP transfers. While some simulation results corroborate the intention of the protocols specifications, other results give insights not easily gained without performing simulations. This study provides a deep understanding of the overall performance of the various protocols and supports the design process of a Mobile IPv6-based network when a decision of whether it is appropriate to implement any of the proposed Mobile IPv6 enhancements has to be made.